DIPG-31. TUMOR SURVEILLANCE USING LIQUID BIOME IN PEDIATRIC HIGH GRADE GLIOMAS. Issue 2 (22nd June 2018) - Bonner, Erin; Panditharatna, Eshini; Kambhampati, Madhuri; Van Gool, Stefaan; Stuecker, Wilfried; Packer, Roger; Nazarian, Javad
Abstract: Immunotherapy is currently being used to treat pediatric brain cancer, though its efficacy in treating patients with diffuse intrinsic pontine glioma (DIPG), the deadliest pediatric brain tumor, has not been evaluated. MRI is the gold standard for monitoring tumor response to therapy, but is limited by pseudoresponse and psuedoprogression: post-treatment, immune cells infiltrate the primary tumor causing transient tumor enlargement, which falsely resembles tumor progression on MRI. Thus, it is critical to develop more accurate approaches to monitor tumor response to immunotherapy. Here, we use a liquid biopsy platform we have already established to monitor tumor response to therapy, to assess whether this platform is sufficient to monitor response to immunotherapy. The most frequent driver mutation in DIPG is the conversion of lysine 27 to methionine in histone H3, encoded by H3 variants H3.3 (H3F3A) and H3.1 (HIST1H3B/C). Here, we report detection of H3F3A mutation allelic frequency (MAF) in circulating tumor DNA in plasma obtained from DIPG patients undergoing immunotherapy with Newcastle disease virus (NDV) vaccine. NDV selectively targets tumor cells and induces immunogenic cell death; we hypothesize that this treatment will decrease tumor burden, corresponding to lower levels of mutant H3F3A and HIST1H3B in plasma. We used our digital droplet PCR liquid biopsy platform to determine histone mutation status (H3.3, H3.1, H3 wild type) at time of diagnosis, and to monitor MAF through the course of treatment, in order to correlate MAF to tumor response. This platform allows for more sensitive, accurate monitoring of tumor response than conventional MRI.